2020
DOI: 10.1002/ddr.21683
|View full text |Cite
|
Sign up to set email alerts
|

Monensin inhibits proliferation, migration, and promotes apoptosis of breast cancer cells via downregulating UBA2

Abstract: Breast cancer is a malignant tumor that occurs in the epithelial tissue of the breast gland, the morbidity, and mortality of which continue to increase. Therefore, it is crucial to find new drugs to treat breast cancer. Monensin is a carrier antibiotic that has been reported to inhibit the growth of cancer cells; however, its impacts on breast cancer cells have not been reported. In this article, the cell survival rate was measured by CCK‐8. Colony formation assay was utilized to detect the level of cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 20 publications
(21 reference statements)
0
15
0
Order By: Relevance
“…UBA2 is a critical subcomponent of E1-activating enzymes and plays a major role in regulating SUMOylation in cellular processes in vivo 40 . Interestingly, UBA2 plays a vital role in multiple diseases, such as colorectal cancer 30 , breast cancer 32 , and lung cancer 33 . However, the role of UBA2 in LSCC tumor progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…UBA2 is a critical subcomponent of E1-activating enzymes and plays a major role in regulating SUMOylation in cellular processes in vivo 40 . Interestingly, UBA2 plays a vital role in multiple diseases, such as colorectal cancer 30 , breast cancer 32 , and lung cancer 33 . However, the role of UBA2 in LSCC tumor progression is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…SAE1 is also closely related to the development of hepatocellular carcinoma, and is helpful for its diagnosis and prognosis [ 29 ]. In addition, UBA2 has been reported to promote the progression of colon cancer, liver cancer, breast cancer, and other tumors [ 30 – 32 ]. In terms of the potential mechanisms, GSEA enrichment results showed that the malignant hallmarks of cancer, including disturbances in DNA replication, the cell cycle, the p53 signaling pathway, mismatch repair, proteasome, and nucleotide excision repair, had significant correlations with the high-risk group.…”
Section: Discussionmentioning
confidence: 99%
“…This proteolytic activity inactivates the Fas receptor and causes apoptosis resistance and chemical resistance to cancer cells or encourages apoptosis of neighbouring cells depending on the method. In addition, proteolytic shedding of tumour-associated major histocompatibility proteins with ADAM17-related complex class-I proteins will inhibit natural killer ( NK) cytotoxicity to cancer cells 49 Matrix metalloproteinase can, in particular, contribute to the anti-apoptotic effect by indirectly activating serine/ threonine kinase Akt / protein kinase B via the EGFR and IGFR signalling cascadesMatrix metalloproteinase also facilitates apoptosis, most likely indirectly by altering the composition of the ECM; for example, by splitting laminin, which affects the signalling of the integrin 50 .…”
Section: Matrix Metalloproteinase and Cancer Cell Apoptosismentioning
confidence: 99%